2017
DOI: 10.7717/peerj.3658
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of carbon nanotubes generated in forest wildfire ecosystems rich in resinous trees on native plants

Abstract: Carbon nanotubes (CNTs) have a broad range of applications and are generally considered human-engineered nanomaterials. However, carbon nanostructures have been found in ice cores and oil wells, suggesting that nature may provide appropriate conditions for CNT synthesis. During forest wildfires, materials such as turpentine and conifer tissues containing iron under high temperatures may create chemical conditions favorable for CNT generation, similar to those in synthetic methods. Here, we show evidence of nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…4), a well-known NO-releasing compound [30,31]. Similar inducing responses were discovered in resinous trees [41], lettuce [42], and Arabidopsis [43] when challenged with MWCNTs (OD 6-13 nm, about 9.5 nm, and 30-40 nm, respectively). For example, the application with either pristine MWCNT (p-MWCNT) or carboxylfunctionalized MWCNT (c-MWCNT) (average diameter 9.5 nm) could promote the development of LR in lettuce seedlings [42].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…4), a well-known NO-releasing compound [30,31]. Similar inducing responses were discovered in resinous trees [41], lettuce [42], and Arabidopsis [43] when challenged with MWCNTs (OD 6-13 nm, about 9.5 nm, and 30-40 nm, respectively). For example, the application with either pristine MWCNT (p-MWCNT) or carboxylfunctionalized MWCNT (c-MWCNT) (average diameter 9.5 nm) could promote the development of LR in lettuce seedlings [42].…”
Section: Discussionsupporting
confidence: 56%
“…Until now, different responses in LR formation, promotion or inhibition, were respectively reported in various plant species when supplemented with nanomaterials, including MWCNTs [40][41][42][43], gold nanoparticles (Au NP, [44]), zinc oxide nanoparticles (ZnO NP [45,46];), titanium dioxide nanoparticles (TiO 2 NP [46];), and graphene oxide (GO [47][48][49];) (Table 1), and no study has yet provided definitive proof of a role of NO in above responses. In this study, the detection of endogenous NO by Greiss reagent method, laser scanning confocal microscopy (LSCM), and electron paramagnetic resonance (EPR) analyses revealed that the NO level was increased in MWCNT-treated tomato seedlings.…”
Section: Introductionmentioning
confidence: 99%
“…The samples (0.5 mg of dry sample) analyzed by Raman spectroscopy were dispersed in 50 μL water, aliquots of 10 μL were placed on slides, five drops for each sample, allowed to dry at room temperature to be analyzed in Raman spectrometer (Lab Ram HR Evolution; Horiba, Kyoto, Japan) with a spectral resolution of 5 cm −1 using a 20-mW He-Ne laser at 632.8 nm visual excitation, and the spectral range was scanned from 110 cm −1 to 3,690 cm −1 with an integration time of 5 s ( Lara-Romero et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…High-resolution transmission electron microscopy (HR-TEM) was performed by using a Philips CM-200 analytical TEM operating at 200 kV. Specimens for HR-TEM analysis were prepared by dispersing the samples in acetone via sonication for 2 min and air-drying a drop of the suspension on a perforated carbon-coated Cu° grid at room temperature ( Lara-Romero et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the ashes obtained were pulverized and suspended in distilled water or used directly for further qualitative and quantitative analyses. The samples (0.5 mg of dry sample) analyzed by Raman spectroscopy were dispersed in 50 μL water, aliquots of 10 μL were placed on slides, five drops for each sample, allowed to dry at room temperature to be analyzed in Raman spectrometer (Lab Ram HR Evolution, Horiba) with a spectral resolution of 5 cm -1 using a 20-mW He-Ne laser at 632.8 nm visual excitation, and the spectral range was scanned from 110 cm -1 to 3690 cm -1 with an integration time of 5 s (Lara-Romero et al 2017). Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy of samples obtained under the aforementioned conditions were analyzed, and the spectra were recorded via a Nicolet iS10 spectrophotometer (Thermo Scientific) by the attenuated total reflection (ATR) technique.…”
Section: Analyses Of Mwcntsmentioning
confidence: 99%